Pengaruh Sistem Distribusi Bantuan Pangan Non Tunai dalam Mensejahterakan Masyarakat Tahun 2021 (Studi Kasus di Kecamatan Sukodadi Kabupaten Lamongan Jawa Timur) - Moh. Sadiyin; Ahmad Burhan Hakim (JOSH: Journal of Sharia, 2022)
Assistance is one of the ways used by the government to slightly ease the economic burden of the community, especially the poor. The government as the executor of state duties does have a goal to carry out and improve the welfare of the community so that the government's functions and roles are clearly visible. In an effort to ease the economic burden on the community, the Indonesian government launched a non-cash food assistance program or abbreviated as BPNT. The aid was intended to ease the economic burden on the community, but in the field, conditions were different. The process of distributing the aid was hampered by an inaccurate data collection process by the aid distributor or the program. So that people who should be asking for help do not receive assistance, and vice versa. From these shortcomings, the final distributor, namely the village government, then makes improvements or updates the data according to the specified criteria. The research method in this paper uses a qualitative method with a case study approach in the Sukodadi District, Lamongan Regency, East Java. Furthermore, from the results of the study, it was concluded that the beneficiaries or referred to as beneficiary families (KPM) were greatly helped by the assistance program. It is the hope of the recipient community that the program can be continued so as to ease their economic burden.